PENGAJARAN PRIBAHASA BAHASA INDONESIA MENGGUNAKAN MODEL PASANGAN MAKNA - Muzakkir Munzir (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2015)
This paper describes theoretical framework on (1) theoretical underpinning of paired meaning, (2) instructional activities explaining proverbs using paired meaning, and (3) identifying benefits and weaknesses of paired meaning techniques.  This paper used content analysis to analyze data.  The analyses showed that (1) paired meaning techniques are a techniques developed upon active teaching-learning. Its implementation integrates two techniques: play and discovery; (2) Teaching techniques are implemented through identifying paired meaning from the proverbs randomly. The search is developed through simulation from paired group or in group; (3) Model of paired meaning has benefits that it improves students’ motivation through games, but it is short of spending too much time in the implementation.